Attunement through the body - Nagatomo, Shigenori (Albany, NY : State University of New York, 1992)
Part 1: Two contemporary Japanese concepts of the body: Ichikawa Hiroshi and Yuasa Yasuo -- 1: Ichikawa's view of the body -- 2: Ichikawa's concept of the body Qua structure -- 3: Yuasa's body scheme -- Part 2: A medieval Japanese concept of the body: Dōgen Kigen -- 4: Buddhism and Dōgen's concept of the body -- 5: Dōgen and the body in meditation -- 6: Dōgen and the body in transformation -- 7: Dōgen and the body in action -- Part 3: A theory of attunement -- 8: Preliminaries and a theory of attunement -- 9: A sketch of a general theory of attunement -- 10: A stratification of engagement.
boek